Discrepancies in Hospital Cost and Indonesia's Case-based Groups: A Literature Review - Skarayadi, Oskar; Endarti, Dwi; Satibi, Satibi; Mukti, Ali Ghufron (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Indonesia started establishing national health insurance in 2014. Implementation of Indonesian national health insurance has frequent gaps between health expenditures based on hospital tariffs and the INA-CBG tariffObjectives: This review was aimed to compare the hospital tariff of healthcare to the INA-CBGs tariff and to identify the factors contributing to the actual cost.Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology followed in this research. The keywords "Real Cost and INA CBG'S" were used in Google Scholar, and the keywords "INA CBG'S AND REAL COST" on Pubmed, ScienceDirect, and Scopus between 2014 and 2022.Results: A total of 634 records were found through database searching of Google Scholar (594), Pubmed (1), ScienceDirect (36), and Scopus (3). After the screening process, 24 articles were included in the review. It was found that 13 articles (54.16%) showed a lower hospital tariff than INA CBG's tariff, while 11 articles (45.84%) showed a higher hospital tariff than INA CBG's tariff. The main factors affecting the gaps of hospital tariff versus INA CBGs tariff mentioned in the articles were LOS, severity, and hospitality class.Conclusion: The literature of this review found hospital rates are higher with rates of INA-CBGs in many hospitals, so it requires a review of rates and an efficient strategy of hospitals.